Mass transfer in bubble column reactors: effect of bubble size distribution - Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2007)
Mass transfer in a bubble column is analyzed in a different perspective. The experiments were performed in a bubble column reactor that was operated in a regime where the overall rate of absorption of gas into liquid was dependent on both the mass-transfer coefficient and the rate of reaction. Homogeneous catalytic oxidation of sodium sulfite was considered as a model reaction. The local instantaneous velocity data was measured using LDA in the presence of reaction and was used to yield the bubble size distribution at several locations in the column. The role of individual bubble size during mass transfer with chemical reaction was observed to vary. The findings suggest that a narrow bubble size distribution would help to achieve uniformity in the performance at bubble scale, so that an identical regime of mass transfer with reaction exists at the individual bubble level.

Mixing of medium viscosity liquids in a stirred tank with fractal impeller - Mule, Gunwant M.; Kulkarni, Amol A. (Theoretical Foundations of Chemical Engineering, 2016)
Mixing of viscous liquids in a stirred tank is a daunting task. The present paper explores the possibility of using a fractal impeller for mixing of viscous liquids in a stirred tank. The analysis includes power consumptions characteristics, mixing characteristics and the flow patterns in the stirred tank. Ultrasonic velocity profiler (UVP) was used to measure the local velocities in the stirred tank. Fractal impeller found to exhibit different power consumption characteristics than known for conventional impellers. For the range of viscosities 0.58-0.192 Pa s, mixing time found to be directly proportional to the power consumption per unit mass. The normalised mean radial velocity profiles were found to be independent of fluid viscosities studied in the present work.

Microwave assisted batch and continuous flow synthesis of palladium supported on magnetic nickel nanocrystals and their evaluation as reusable catalyst - Nikam, Arun V.; Kulkarni, Amol A.; Prasad, Bhagavatula L. V. (Crystal Growth & Design, 2017)
Palladium nanocrystals (NCs) supported on nickel NCs (Pd/Ni) were synthesized in a continuous flow manner by the microwave-assisted method in the presence and absence of oleylamine. Parameters optimized for batch experiments were considered while performing continuous flow synthesis. The Pd/Ni NCs synthesized in the presence of oleylamine displayed good catalytic activity for hydrogenation of aromatic nitro compounds, and those bearing alkene, and alkyne moieties. The ferromagnetic character of the supporting nickel NCs allowed the recovery of the catalyst and these recovered catalysts could be reused several times.

Multi-step continuous flow synthesis of the cystic fibrosis medicine ivacaftor - Vasudevan, N.; Sharma, Mrityunjay K.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2018)
A continuous flow ozonolysis method combined with a multi-step flow sequence is developed for the synthesis of the drug ivacaftor for the first time. Safe ozonolysis, a continuous flow quadruple reaction to construct a quinolone scaffold, and inline extraction followed by continuous phase separation are the key features of the present work. The feasibility of using a continuous mixed flow reactor, commonly referred to as a continuous stirred tank reactor (CSTR), is also investigated for the relatively slow reaction step. The current integrated multi-step flow synthesis can produce 7.2 g of the drug ivacaftor per day on a laboratory scale, which is sufficient to treat 50 patients per day. The present route can also be used as a general route for the synthesis of other related drugs such as quinolone antibiotics.

Multi-step synthesis of miltefosine: integration of flow chemistry with continuous mechanochemistry - Patil, Niteen B.; Atapalkar, Ranjit S.; Chavan, Subhash P.; Kulkarni, Amol A. (Chemistry-A European Journal, 2021)
Herein we report for the first time, an advanced continuous flow synthesis of the blockbuster Leishmaniasis drug miltefosine from simple starting materials by a sequence involving four steps of chemical transformation including a continuous mechanochemical step. First three reaction steps were performed in simple tubular reactors in a telescopic mode, while in the last step the product precipitated from the 3(rd) step was used for a continuous mechanochemical synthesis of miltefosine. When compared to a typical batch protocol that takes 15 h, miltefosine was obtained in 58 % overall yield in flow synthesis mode at the laboratory scale in a total residence time 34 min at synthesis rate of 10 g/hr, which is sufficient to treat 4800 patients per day.
Keywords: continuous flow; continuous mechanochemistry; miltefosine; multistep synthesis; reactive intermediates

Model predicted optimization of experimental set-up and process conditions for microwave-assisted synthesis of silver nanowires - Sonawane, Jayesh R.; Kulkarni, Amol A. (Chemical Engineering Journal, 2024)
This work presents simulations led optimization of choice of a reactor for an experimental set-up for the continuous production of silver nanowires with certain constraints in terms of yield, reaction time, and dimensions of nanowires. The choice of reactors based on the simulations of reaction kinetics for nucleation and growth phases of driving the optimization of an experimental set-up and subsequent optimization of process conditions to maximize the yield of nanowires of desired dimensions. The optimized reactor configuration is dictated by the reaction kinetics and using a microwave in continuous mode becomes unavoidable. This makes the approach highly reproducible as well as scalable. The integration of conventional and microwave heating is simulated and subsequently optimized experimentally to attain a significant increase in nanowire yield under steady-state conditions with less than 15 min of residence time. The precise control over the rate in different reactor configurations governing nucleation, accelerated growth followed by slow growth to complete the conversion of precursor enables higher selectivity of nanowires with controllable dimensions resulting in 100 gm production per day using simple set-up. We systematically examined key reaction parameters, including the concentration of metal ions, residence time, and different reactor configurations. Our approach successfully yielded AgNWs with 40-60 nm diameter and 15 mu m length. The cost associated with this process for synthesizing AgNWs is less than 10\$ per gram. This study highlights the potential of continuous, high-throughput processes for controlling nanowire size and yield through advanced reactor engineering.
Keywords: Continuous synthesis; Microwave; Reactor design; Silver Nanowires